Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.jpcc.0c05911
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Mechanism of Enhanced Performance of In-Ga-Zn-O Thin-Film Transistors with Nanometer Thicknesses under Temperature Stress

Abstract: In-Ga-Zn-O (IGZO) nanometer thin-film transistors (TFTs) are promising candidates for liquid crystal display (LCD) drivers and human body sensors. It is critically important to study the temperature dependence of IGZO TFTs on electrical properties. However, the mechanism of the enhanced IGZO TFT function at different temperatures has not been fully determined. Here, a single transistor was used to act as a temperature sensor to save the space, and transfer curves shifting positively were found for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…The occupation probability f (E) describes that traps are either filled with electrons or empty; then, it has a value in the range of 0 to 1, and consequently the Fermi energy position can be determined when f (E) = 0.5. The occupation probability f (E) and thermal velocity υ n and υ p for the electron and hole in Equations ( 9) and ( 10) can be determined by assuming the Richardson coefficients (A n , A p ) of 41 A•cm −2 •k −2 [29], capture cross sections σ E and σ H of 1 × 10 12 cm 2 [30], and conduction/valance band effective density of states (N C = N V ) of 2.0 × 10 18 cm −3 , initially estimated from the carrier concentration of Hall measurements.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The occupation probability f (E) describes that traps are either filled with electrons or empty; then, it has a value in the range of 0 to 1, and consequently the Fermi energy position can be determined when f (E) = 0.5. The occupation probability f (E) and thermal velocity υ n and υ p for the electron and hole in Equations ( 9) and ( 10) can be determined by assuming the Richardson coefficients (A n , A p ) of 41 A•cm −2 •k −2 [29], capture cross sections σ E and σ H of 1 × 10 12 cm 2 [30], and conduction/valance band effective density of states (N C = N V ) of 2.0 × 10 18 cm −3 , initially estimated from the carrier concentration of Hall measurements.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Although a-IGZO TFT technology has made remarkable progress since it was first proposed by Nomura et al in 2004, these devices still cannot achieve the desired performance and reliability due to high-density sub-gap states existing in the bandgap of a-IGZO [4,5]. It has been demonstrated that the sub-gap defects mainly originate from oxygen-vacancyrelated (V o -related) defects induced by the structural disorder in a-IGZO [5][6][7], which degrades the electrical properties and reliability of TFTs by trapping electrons or holes in the channel layer and interfacial region under bias, light, and thermal stress [8][9][10][11]. To enhance the device performance and reliability, an in-situ nitrogen-doping (N-doping) approach during the a-IGZO active layer deposition has been proposed to suppress V o defect generation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%